2019
DOI: 10.1108/ribs-10-2018-0089
|View full text |Cite
|
Sign up to set email alerts
|

Absorptive capacity and organizational mechanisms

Abstract: Purpose This study aims to contribute to fill the gap in the existing absorptive capacity (AC) literature relating to how organizational mechanisms applied both at the national and international level affect a firm’s AC. Design/methodology/approach A systematic literature review was carried out using analytical articles from two sources – Web of Science and Scopus – aiming to cover as many studies related to the AC research topic. Findings The results show that the majority of the studies do not include a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…We also adopt and broaden absorptive capacity theory (Cohen and Levinthal, 1990) by investigating a moderating role of the firm’s green technological capabilities. Some scholars report that internal and external knowledge have complementary relations and both can help a firm achieve better innovation (Cordero and Ferreira, 2019; Cassiman and Veugelers, 2002). On the other hand, it is reported that internal R&D might substitute for external knowledge search activities (Laursen and Salter, 2006) or an inverted U-shaped relationship between them (Song and Shin, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also adopt and broaden absorptive capacity theory (Cohen and Levinthal, 1990) by investigating a moderating role of the firm’s green technological capabilities. Some scholars report that internal and external knowledge have complementary relations and both can help a firm achieve better innovation (Cordero and Ferreira, 2019; Cassiman and Veugelers, 2002). On the other hand, it is reported that internal R&D might substitute for external knowledge search activities (Laursen and Salter, 2006) or an inverted U-shaped relationship between them (Song and Shin, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A firm’s internal technological capabilities may have a complementary and/or a substitutive relationship with external knowledge sourcing. Many scholars argue for a complementary relationship between a firm’s internal technological capability and external knowledge sourcing, which results in a better innovation performance (Cordero and Ferreira, 2019; Cassiman and Veugelers, 2002; Song et al , 2018). Rothwell (1992) emphasizes how scientists and skilled labor, a well-prepared organization and openness to external knowledge sources can increase absorptive capacity.…”
Section: Theory Development and Hypothesesmentioning
confidence: 99%
“…In addition, SCC also contains supporting entities (e.g., governmental agencies and research institutes) that enhance overall cluster development as they provide training and technical support [3]. This supports organisations' ability to adapt to changes and make use of opportunities [38,40,41]. In turn, it facilitates their development of absorptive capacity [12] and resilience [20,37], especially since collaboration and governance among organisations support supply chain dynamic capabilities [42].…”
Section: Relationship Between Sccdcs and Dcsmentioning
confidence: 99%
“…Numerous studies on business performance have been conducted in the field of business management, strategy, knowledge management and other related fields since the authors of [19] first introduced the concept of ACAP in 1990 [21]. However, despite the existence of a large number of studies addressing them, the literature on this topic is confronted with an "ambiguity problem" mainly about conceptualisation as well as measurement.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the existence of a large number of studies addressing them, the literature on this topic is confronted with an "ambiguity problem" mainly about conceptualisation as well as measurement. This is because researchers have used ACAP as a general-purpose construct, overlooking previous studies on the topic that have presented, for example, its multidimensional nature, among other relevant theories, and because of the lack of understanding of the nature of the construct itself [18,21]. Furthermore, few studies examine ACAP in depth [20], despite that, of all the dynamic capabilities, ACAP is among the so-called high-level capabilities, as it serves to explain both the success and failure of a company, in addition to favouring the creation of wealth and participation in the creation of a competitive advantage over time [22].…”
Section: Introductionmentioning
confidence: 99%